Effects of two different types of ankle–foot orthoses on gait outcomes in patients with subacute stroke: a randomized crossover trial. (August 2020) - Karakkattil, Priya Sibi; Trudelle-Jackson, Elaine; Medley, Ann; Swank, Chad
Objective: To identify whether patients in the subacute stage of stroke, with foot drop, would have better gait outcomes when using a double-adjustable AFO (DA AFO) or a posterior leaf spring AFO (PLS AFO) at baseline without practice and to determine whether one week of practice would significantly change gait outcomes with either of the AFOs. Design: Within-subject 2 × 2 repeated measures design. Setting: Postacute and outpatient rehabilitation center. Participants: Twenty individuals with mean age of 57 years (SD: 12.0 years) with subacute stroke. Interventions: Participants were measured using DA AFO and PLS AFO at baseline. Follow-up measurements were taken after one week of practice with each type of AFO in randomly assigned order. Outcome Measures: Gait endurance (6-Minute Walk Test (6MWT)), gait symmetry, and gait velocity at self-selected and fast-paced velocity measured using GAITRite gait analysis system and patient report of AFO preference. Results: At baseline, no significant differences were found between the 2 AFOs ( P > 0.05). There was no significant interaction ( P > 0.05) of AFO and practice for gait endurance, symmetry, and velocity. Main effect of practice was significant for gait endurance ( P < 0.001), self-selected velocity ( P = 0.001), and fast-paced velocity ( P < 0.001). In all, 16 participants preferred using DA AFO for walking. Conclusions: No difference between DA AFO and PLS AFO was found on measures of gait endurance, symmetry, and velocity at baseline or after practice. With practice over time, participants improved in gait endurance and velocity regardless of AFO type.